Developmental Relationships of Four Exhausted CD8 + T Cell Subsets Reveals Underlying Transcriptional and Epigenetic Landscape Control Mechanisms - Beltra, Jean-Christophe; Manne, Sasikanth; Abdel-Hakeem, Mohamed S; Kurachi, Makoto; Giles, Josephine R; Chen, Zeyu; Casella, Valentina; Ngiow, Shin Foong; Khan, Omar; Huang, Yinghui Jane; Yan, Patrick; Nzingha, Kito; et al. (Immunity (Cambridge, Mass.), 2020)
CD8 T cell exhaustion is a major barrier to current anti-cancer immunotherapies. Despite this, the developmental biology of exhausted CD8 T cells (Tex) remains poorly defined, restraining improvement of strategies aimed at "re-invigorating" Tex cells. Here, we defined a four-cell-stage developmental framework for Tex cells. Two TCF1 progenitor subsets were identified, one tissue restricted and quiescent and one more blood accessible, that gradually lost TCF1 as it divided and converted to a third intermediate Tex subset. This intermediate subset re-engaged some effector biology and increased upon PD-L1 blockade but ultimately converted into a fourth, terminally exhausted subset. By using transcriptional and epigenetic analyses, we identified the control mechanisms underlying subset transitions and defined a key interplay between TCF1, T-bet, and Tox in the process. These data reveal a four-stage developmental hierarchy for Tex cells and define the molecular, transcriptional, and epigenetic mechanisms that could provide opportunities to improve cancer immunotherapy.